Persistent Circulation of Enterohemorrhagic Escherichia coli (EHEC) O157:H7 in Cattle Farms: Characterization of Enterohemorrhagic Escherichia coli O157:H7 Strains and Fecal Microbial Communities of Bovine Shedders and Non-shedders - Bibbal, Delphine; Ruiz, Philippe; Sapountzis, Panagiotis; Mazuy-Cruchaudet, Christine; Loukiadis, Estelle; Auvray, Frédéric; Forano, Evelyne; Brugère, Hubert (Frontiers in Veterinary Science, 2022)
Cattle are carriers, without clinical manifestations, of enterohemorrhagic Escherichia coli (EHEC) O157:H7 responsible for life-threatening infections in humans. A better identification of factors playing a role in maintaining persistence of such strains in cattle is required to develop more effective control measures. Hence, we conducted a study to identify farms with a persistent circulation of EHEC O157:H7. Two farms which had previously provided carriers at slaughter were still housing positive young bulls, and this was true over a one-year period. Only one fecal sample could be considered from a super-shedder; and 60 % of the carriers shed concentrations below 10 MPN/g. Moreover, EHEC O157:H7 represented minor subpopulations of E. coli. PFGE analysis of the EHEC O157:H7 strains showed that persistent circulation was due either to the persistence of a few predominant strains or to the repeated exposure of cattle to various strains. Finally, we compared fecal microbial communities of shedders (S) and non-shedders (NS) from one farm. Regarding alpha diversity, no significant difference between S vs NS was observed. At the genus level, we identified 10 Amplicon Sequence Variants (ASVs)’ indicators of the S or NS groups. In conclusion, the characteristics enhancing the persistence of some predominant strains observed here should be explored further, and researches focused on mechanisms of competition among E. coli strains are also needed.